The Implementation Of Ladm Versionedobject Class For Representing Spatio-Temporal Of Cadastre 4d Objects - Miranty N. Sulistyawati; Trias Aditya; Purnama B Santosa (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2018)
Abstract: Spatial representations and ownerships of 3D properties change over time. Changes are recorded as historical data of transactions, adding the dimension of 3D spatial data into 4D data, known as Cadastre 4D. Spatial representations of 3D properties are prone to disputes when the shape and dimensions representing ownership changes do not match with the reality. This paper focuses in assessing visualizations of 4D cadastre objects applying VersionedObject class stated in the International Standard of Land Administration Domain Model (ISO 19152:2012). Based on the analysis on the current strata title ownership registration implemented in Indonesia’s land Information System (known as KKP), a model of 4D spatial data that f its to the administration system in Indonesia was developed. Visualization of 4D cadastre objects applied in this research is suited to VersionedObject class LADM and presented on the web to represent changes of 3D geometry boundaries over time.Keywords: Cadastre 3D and 4D, VersionedObject, LADM, data presentation, land information system Intisari: Penyajian spasial dan kepemilikan properti 3D mengalami perubahan dari waktu ke waktu. Perubahan dicatat sebagai data historis transaksi, dengan menambahkan dimensi data spasial 3D ke dalam data 4D, yang dikenal sebagai Kadaster 4D. Representasi spasial properti 3D rentan terhadap sengketa ketika bentuk dan dimensi yang mewakili perubahan kepemilikan tidak sesuai dengan kenyataan. Paper ini berfokus pada visualisasi data spasial obyek kadaster 4D dengan menerapkan kelas VersionedObject LADM (ISO 19152:2012). Berdasarkan analisis pada pendaftaran kepemilikan atas satuan rumah susun terkini yang telah diterapkan di Sistem Informasi Tanah Indonesia (dikenal sebagai KKP), telah dikembangkan model data spasial 4D yang sesuai dengan sistem administrasi di Indonesia. Visualisasi objek kadaster 4D yang digunakan dalam penelitian ini sesuai dengan kelas VersionedObject LADM dan disajikan di web untuk mewakili perubahan batas geometri 3D dari waktu ke waktu.Kata Kunci: Kadaster 3D dan 4D, VersionedObject, LADM, penyajian data, sistem informasi pertanahan